3D MRI of the Hip Joint: Technical Considerations, Advantages, Applications, and Current Perspectives - Ashikyan, Oganes; Wells, Joel; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2021)
Magnetic resonance imaging (MRI) is a common choice among various imaging modalities for the evaluation of hip conditions. Conventional MRI with two-dimensional acquisitions requires a significant amount of time and is limited by partial-volume artifacts and suboptimal fluid-to-cartilage contrast. Recent hardware and software advances have resulted in development of novel isotropic three-dimensional (3D) single-acquisition protocols that cover the volume of the entire hip and can be reconstructed in arbitrary planes for submillimeter assessment of bony and labro-cartilaginous structures in their planes of orientation. This technique facilitates superior identification of small labral tears and other hip lesions with better correlations with arthroscopy. In this review, we discuss technical details related to 3D MRI of the hip, its advantages, and its role in commonly encountered painful conditions that can be evaluated with great precision using this technology. The entities described are femoroacetabular impingement with acetabular labral tears, acetabular dysplasia, avascular necrosis, regional tendinopathies and tendon tears, bursitis, and other conditions.
Keywords: hip; isotropic 3D MRI; acetabular dysplasia; femoroacetabular impingement